2014
DOI: 10.1007/s10147-014-0734-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glucosylceramides suppress tumor growth in a mouse xenograft model of head and neck squamous cell carcinoma by the inhibition of angiogenesis through an increase in ceramide

Abstract: These results suggest that dietary glucosylceramides trigger the de novo pathway of ceramide synthesis, indicating that sphingosine-based ceramide suppresses the growth of head and neck tumors through the inhibition of pro-angiogenic signals such as VEGF, VEGF receptor-2, and HIF-1α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Sphingolipids and ceramides were the only groups of lipid-related biochemicals that were decreased in maternal plasma due to diabetes mellitus. Regulation of the sphingolipid and ceramide pathway affects angiogenesis and impairs endothelial function and the remodelling of maternal spiral arteries that occurs in preeclampsia [52,53]. Preeclampsia is associated with diabetes mellitus [54,55].…”
Section: Diabetic Dysregulation Of Maternal and Embryonic Lipid Metabmentioning
confidence: 99%
“…Sphingolipids and ceramides were the only groups of lipid-related biochemicals that were decreased in maternal plasma due to diabetes mellitus. Regulation of the sphingolipid and ceramide pathway affects angiogenesis and impairs endothelial function and the remodelling of maternal spiral arteries that occurs in preeclampsia [52,53]. Preeclampsia is associated with diabetes mellitus [54,55].…”
Section: Diabetic Dysregulation Of Maternal and Embryonic Lipid Metabmentioning
confidence: 99%
“…For example, the dietary intake of glucosylceramide prevents colon preneoplastic lesions [15] and head and neck cancers [16,17]. Also, when administered to the skin, it improves skin disorders [18].…”
Section: Introductionmentioning
confidence: 99%
“…24 Further, dietary Glu-Cer suppressed tumor growth in a mouse xenograft model of HNSCC by inhibiting angiogenesis through an increase in ceramide, and dietary Glu-Cer was synthesized by a de novo pathway after digestion absorption, thus raising the blood level of ceramide. 25 The inhibitory effect of Glu-Cer on colon tumorigenesis has previously been reported. Inamine et al showed that dietary Glu-Cer had potential chemopreventive effects in short-term colon carcinogenesis bioassays in rats, inhibiting the formation of preneoplastic lesions such as aberrant crypt foci and β-catenin-accumulated crypts.…”
Section: Introductionmentioning
confidence: 87%